1995
DOI: 10.1111/j.1464-410x.1995.tb07782.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum granulocyte colony‐stimulating factor levels in patients with urinary bladder tumour and various urological malignancies

Abstract: These results suggest that elevated serum G-CSF level might be associated with a poor prognosis in patients with UBT and be due to the production of G-CSF by UBT cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…
topoietic cytokines in various malignant diseases, and has generally been considered to reflect the aggressive nature of the tumor and a poor clinical outcome [1] . Herein, we report the first case of prostate cancer producing granulocyte colony-stimulating factor (G-CSF), with an unusual clinical course and immunohistochemical analyses.
Case Report

An 86-year-old man presented with urination difficulties in June 2003.

…”
mentioning
confidence: 99%
“…
topoietic cytokines in various malignant diseases, and has generally been considered to reflect the aggressive nature of the tumor and a poor clinical outcome [1] . Herein, we report the first case of prostate cancer producing granulocyte colony-stimulating factor (G-CSF), with an unusual clinical course and immunohistochemical analyses.
Case Report

An 86-year-old man presented with urination difficulties in June 2003.

…”
mentioning
confidence: 99%
“…In addition, numerous studies have demonstrated that some human bladder cancers may produce G-CSF frequently, presenting leukaemoid reactions (Mizutani et al, 1995). Furthermore, G-CSF production in vitro was demonstrated in another bladder cancer cell line (5637) that is used as a source of G-CSF (Bailly et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The NSGCT cell lines secreted G-CSF at levels comparable with those measured in the supernatant from some UBT cells (2/4 cell lines 240±23550 pg/ml and 2/4 cell lines <30 pg/ml; Mizutani et al 1995). Both the cell lines producing G-CSF and/or GM-CSF are clones of the multi-potential EC cell line 1777NRp (Bronson et al 1984), which were isolated be D. Bronson following lowdensity passage of 1777NRp (1777NRp Cl-A; Bronson et al 1983Bronson et al 1984;Casper et al paper submitted).…”
Section: Discussioǹ`hmentioning
confidence: 93%
“…In patients with urinary bladder tumour (UBT) an elevated serum G-CSF level has been suggested to be associated with a poor prognosis, the G-CSF being produced by UBT cells (Mizutani et al 1995). IL-6 serum levels have been correlated with the disease status and/or prognosis in patients with renal cell (Blay et al 1992), esophageal (Oka et al 1996), gastric (Wu et al 1996) and ovarian (Berek et al 1991) carcinomas.…”
Section: Introductionmentioning
confidence: 99%